Establecer en el Código de la Niñez y Adolescencia que la tenencia se deba extender a otros parientes cercanos en caso de que ninguno de los dos padres pueda ejercerla - Morales Cupacan, Jacinto Oswaldo (2015)
The constitution guarantees the right to a family and protects its regulatory body; because the family is considered that fundamental cell of society; but there are occasions in which families are overshadowed by a number of circumstances, such as parental divorce, migration, disabilities that prevent parents care for their children, or as unfortunate death; this causes the family is destroyed, it distances itself, it looks fractionated by these developments. From everything mentioned it is unfortunate when there minor children who are unprotected or unsuitable people care for proper development of the child or adolescent as mentioned in the Constitution. The Code for Children and Adolescents, is limited as Article 118 states that "When the judge deems most appropriate for the development of the child family, entrust their care and upbringing to one of the parents (... ..) "As evidence of that article mentions only the rules that care be entrusted with one parent and does not extend to family tenure is granted. The legislator has not noticed that for some reason children may be left without a father or mother (parents), violating and restricting the right to have a family as provided by the Constitution. That is why the face of uncertainty and pretending to protect the rights of children I plan to perform primarily a conceptual analysis, doctrinal, legal compared tenure, who can exercise and countless circumstances seen in this legal instrument that is of transcendental importance because it refers to a vulnerable group which for a good development needs a family that gives them love, protection, care, provide them with adequate food for their growth.